Life-Threatening Irinotecan-Induced Toxicity in an Adult Patient with Alveolar Rhabdomyosarcoma: The Role of a UGT1A1 Polymorphism. (26th September 2017) - Jannin, Arnaud; Hennart, Benjamin; Adenis, Antoine; Chauffert, Bruno; Penel, Nicolas
Abstract : Alveolar rhabdomyosarcoma (AR) in adult patients is an exceptional malignancy. Management of AR is based on (neo)adjuvant chemotherapy combining ifosfamide, vincristine, and actinomycin D and local curative-intent surgery/radiotherapy. In cases of relapsing AR, the combination of temozolomide/irinotecan is regarded as a possible option. Here we describe life-threatening long-lasting toxicity related to the 1st cycle of irinotecan-based chemotherapy in a 56-year-old woman suffering from locally advanced and metastatic head and neck AR. The patient experienced grade 4 vomiting and diarrheas resulting in acute functional renal failure, associated with grade 4 neutropenia complicated by severe septic shock. The hospital stay duration was 40 days. The analysis of the uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) gene revealed homozygous UGT1A1 ⁎ 28 polymorphism with an associated homozygous mutation c.-3275T>G; the latter is associated with a decrease of about 80% of UGT1A1 transcription explaining this irinotecan induced toxicity. Physician must be aware of the potential hematological (mainly neutropenia and infectious disease) and digestive (mainly diarrhea) toxicities caused by irinotecan and especially when the patient presents a UGT1A1 ⁎ 28 homozygous allele. UGT1A genotyping performed before initiating treatment is useful to anticipate severe toxic reaction to irinotecan and improve the benefit/risk ratio of its use.